2016
DOI: 10.1016/j.molp.2016.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Transmembrane Helices within Monomers of the Aquaporin AtPIP2;1 Play a Crucial Role in Tetramer Formation

Abstract: Aquaporin (AQP) is a water channel protein found in various subcellular membranes of both prokaryotic and eukaryotic cells. The physiological functions of AQPs have been elucidated in many organisms. However, understanding their biogenesis remains elusive, particularly regarding how they assemble into tetramers. Here, we investigated the amino acid residues involved in the tetramer formation of the Arabidopsis plasma membrane AQP AtPIP2;1 using extensive amino acid substitution mutagenesis. The mutant proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…It shows enhanced interactions with Ile-190, Thr-194, Phe-220 and Ala-221 from the TM4-TM5 region of ZmPIP1;2 (Figure 7A). Such extensive interactions are not possible for the small residue Ala. Based on the mutation studies, Yoo et al 50 have concluded that Ile-93 is important to stabilize the TM5 conformation at the monomer-monomer interface. However, they studied the importance of residues in tetramer formation of AtPIP2;1 homotetramers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It shows enhanced interactions with Ile-190, Thr-194, Phe-220 and Ala-221 from the TM4-TM5 region of ZmPIP1;2 (Figure 7A). Such extensive interactions are not possible for the small residue Ala. Based on the mutation studies, Yoo et al 50 have concluded that Ile-93 is important to stabilize the TM5 conformation at the monomer-monomer interface. However, they studied the importance of residues in tetramer formation of AtPIP2;1 homotetramers.…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that the formation of homo- and hetero-tetramers can modulate the water permeability of the cell plasma membrane. Yoo et al 50 carried out extensive mutagenesis studies on Arabidopsis PIP2;1 to identify residues that could play important role in tetramer formation. Their studies indicated that residues in TM1, TM2 and TM5 involved in transmembrane helix-helix interactions within and between monomers are critical in tetramer assembly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By using a protein known to be targeted to the plasma membrane (AtPIP2A; Yoo et al, 2016), it was resolved that PvSUT1.1 co-localizes with the AtPIP2A control, thus confirming that PvSUT1.1 is targeted to the plasma membrane. It is also apparent that GFP seems to also be present in the nuclei and the cytosol, which is where free GFP is usually found (Brandizzi et al, 2003).…”
Section: Pvsut11 Is Targeted To the Plasma Membranementioning
confidence: 92%
“…A confocal microscope (Olympus FluoView TM FV1000) was used to take images of leaf epidermal cells two days after infiltration. As plasma membrane control, Arabidopsis PIP2A (At3g53420; Yoo et al, 2016) fused to mCherry (Shaner et al, 2004) was used.…”
Section: Subcellular Localizationmentioning
confidence: 99%